2015
DOI: 10.3171/2015.3.jns131356
|View full text |Cite
|
Sign up to set email alerts
|

Treatment biases in traumatic neurosurgical care: a retrospective study of the Nationwide Inpatient Sample from 1998 to 2009

Abstract: OBJECT This study was designed to assess the relationship between insurance status and likelihood of receiving a neurosurgical procedure following admission for either extraaxial intracranial hemorrhage or spinal vertebral fracture. METHODS A retrospective analysis of the Nationwide Inpatient Sample (NIS; 1998–2009) was performed. Cases of traumatic extraaxial intracranial hematoma and spinal vertebral fracture were identified using International Classification of Diseases, Ninth Revision (ICD-9) diagnosis co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 22 publications
0
7
0
1
Order By: Relevance
“…This nationally representative resource encompasses more than 7 million annual inpatient hospitalizations, representing approximately 20% of discharges in the United States . This resource is representative of a significant portion of U.S. inpatient facilities (rehabilitation facilities, federal institutions, and long‐term acute care facilities are excluded), and has been used in numerous studies covering a wide range of topics …”
Section: Methodsmentioning
confidence: 99%
“…This nationally representative resource encompasses more than 7 million annual inpatient hospitalizations, representing approximately 20% of discharges in the United States . This resource is representative of a significant portion of U.S. inpatient facilities (rehabilitation facilities, federal institutions, and long‐term acute care facilities are excluded), and has been used in numerous studies covering a wide range of topics …”
Section: Methodsmentioning
confidence: 99%
“…The NIS has been used to analyze national trends in healthcare use and charges, in quality and outcomes, and in policy. 15,16,22,23,28,32,44 For this study, we used NIS data from 1998 to 2015.…”
Section: Data Sourcementioning
confidence: 99%
“…The same study found Medicare patients were signi cantly less likely to receive surgical treatment. McCutcheon et al [22] found a similar nding where uninsured patients demonstrated both a reduced likelihood of receiving a craniotomy for intracranial hematomas and an increased riskadjusted mortality rate relative to insured patients.…”
Section: Discussionmentioning
confidence: 84%